Tourism planning and development for sustainability - Kaseje, Margaret (Strathmore University, 2014)
The secret to success in both the expansion of international hotel chains and the initial positive results from eco-hospitality by the end of the 1980s was due to the application of the fundamental principles of tourism planning and development which stresses on involvement of key stakeholders in the planning process. Hotel administrations that are concerned with ecology must plan and take action towards preserving the environment by collaborating with communities and key stakeholders. These include the entire hotel operations and related establishments, along with employees at all levels, investors, architects, engineers, ecologists, and others who are interested in preserving nature. Governments and organizations engaged in tourism need to work together to guarantee that tourism is planned, developed and regulated in order to control its impact on nature and to maintain natural resources. This paper explores the main components of tourism planning and development processes, starting from the nature of planning, the various planning approaches and the ways that these broad approaches are implemented, and ends with a review of the outputs and outcomes in Kenya‟s Tourism in the Western Circuit. A tourism planning and development model is proposed that planners and investors can use for evaluating whether or not the objectives of tourism and its sustainability have been achieved.
Conference paper presented at the 1st African Conference on Sustainable Tourism in Strathmore University, Kenya.
Keywords: Tourism planning and development; Sustainability